The optimally mobile Muslim experts in the service of the Ummah. - Muyibi, Suleyman Aremu; Jami, Mohammed Saedi (IIUM Press, 2011)
This paper presents a proposal on how the Muslim Experts made up of Academics, Professionals and Entrepreneurs can be made optimally mobile to utilize their Allah endowed resources to serve the Ummah and mankind more efficiently and effectively as well as being key players in a world which has become a “Global Village”. Some case studies are presented to illustrate some of the major problems facing the Muslim Ummah today in not being able to utilize optimally the human as well as material resources endowed to us by Allah to enable us fulfill our role as the “best of Ummah” created for the benefit of mankind and vicegerent of Allah. This proposal includes the setting up of an International Organization of Optimally Mobile Muslim Experts (IOOMME). It is envisaged that IOOMME will have a Talent Bank which will be a database on Muslim Academics and Professionals living and working in both Muslim and non-Muslim countries with detailed information about the experts, their areas of expertise and products developed etc. Furthermore professional resource centers which will be land-based as well as cyberspace or virtual based will be setup made up of published information (journals, technical reports) and specialized research equipment/facilities available in Muslim nations where Muslim Academics and Professionals can have access to for their use as well as for developing upcoming Muslim Academics and Professionals. It is envisaged that Muslim nations will create the enabling environment through entry visa and professional short visit regulations for Muslim academics and professionals to use their Sabbaticals, annual vacations, study/research leave, professional short visits etc. academic/ professional staff exchange to go to Muslim nations to render their service to the Ummah.